Hospitalization Pattern and Mortality of Patients on Maintenance Hemodialysis in a Low Resources Setting - Maimouna, Mahamat; Teuwafeu, Denis Georges; Mambap Tatang, Alex; Mininamou, Marius; Fouda Menye, Hermine; Kaze Folefack, François; Ashuntantang, Gloria (HEALTH RESEARCH IN AFRICA, 2023)
ABSTRACT Background. Haemodialysis (HD) treatment is challenging in developing countries and could be associated with higher morbidity and mortality. The aim of this study was to describe causes of hospital admission in patients on maintenance HD and factors associated with fatal outcomes. Methods. This cross-sectional, study was conducted in a tertiary care hospital in Cameroon during from 1rst January 2018 to 31rst March 2020. We used files of all patients on maintenance HD admitted during the study period to collect sociodemographic, clinical and paraclinical data. Results. we included 77 patients (77.7% male) with a mean age of 48.7 ± 15.6 years and a median [IQR] dialysis vintage of 30.38 months [3-96]. Vascular access was mainly permanent (72.7%). Hypertension (84.4%) was the most common comorbidity. Hypertension (28.6%), Chronic Glomerulonephritis (27.3%) and diabetes (24.7%) were the main baseline nephropathies. The main causes of hospitalization were infectious (67.5%), neurovascular (18.2%) and digestive (10.4%) diseases. Infectious state was dominated by vascular access infection (25.9%), pneumonia (13%) and malaria (17.3%). Fatality rate was 14.3% due to a sepsis in 90.9%. Out nephrology service admission (RR= 28.34; p=0,041) and use of temporary catheter vascular access (RR = 5.98; p = 0,038) were associated with mortality. Conclusion. Infectious diseases are common in HD patients in this setting and associated with a high risk of mortality. A temporary catheter is associated with a poor outcome. RÉSUMÉ Introduction. L’hémodialyse (HD) reste un véritable challenge en Afrique Subsaharienne où la mortalité est élevée. Le but de cette étude était d’évaluer les motifs d’hospitalisation et le devenir des patients en HD chronique. Methodes: Il s’agissait d’une étude rétrospective monocentrique conduite du 1er janvier 2018 au 31 mars 2020 dans un service d’hémodialyse spécialisé de la capitale politique Camerounaise. Ont été inclus les dossiers des patients adultes en hémodialyse depuis plus de 3 mois et admis en hospitalisation durant la période d’étude. Les données sociodémographiques, cliniques et paracliniques d’interêt ont été colligés. Les considerations éthiques ont été respectées. Un seuil de significativité p<0,05 était considéré comme statistiquement significatif. Résultats. Au total, 77 patients ont été inclus (77,7% sexe masculin) ayant un âge moyen de 48,7 ± 15,6 ans et une durée médiane [IIQ] en dialyse de 30,38 months [3-96]. La majorité des participants (72,7%) avaient un abord vasculaire permanent. L’hypertension artérielle (84,4%) était la principale comorbidité. Les principals causes d’hospitalisations étaient infectieuses (67,5%), neurovasculaires (18,2%) et digestives (10,4%). Les infections incluaient celles des abords vasculaires (38,5%), la pneumonie (19,2%) et le paludisme (17,3%). Le taux de mortalité était de 14,3%, lié au sepsis dans 90,9%. L’admission hors service de néphrologie (RR= 28.34; p=0,041) et l’utilisation d’un cathéter central temporaire (RR = 5.98; p=0,038) étaient associées au décès. Conclusion. La promotion d’un abord vasculaire permanent en HD chronique et une prise en charge multidisciplinaire axée sur les particularités du patients en HD sont à implémenter en vue d’améliorer le pronostic.